E-Commerce dan Implikasinya terhadap Pasar Tradisional Gondanglegi Kab. Malang - Wahab, Fatkhul; Annissah, Roudhotul (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2025)
Traditional markets are vital elements of the local economy and culture. They serve not only as hubs for daily trade but also as spaces for social interaction, cultural preservation, and a source of livelihood for Micro, Small, and Medium Enterprises (MSMEs). However, the existence of traditional markets is currently threatened by the dominance of modern markets and the rise of e-commerce. The shift in consumer behavior toward online shopping has led to a decline in foot traffic and threatens the sustainability of traditional markets. This study aims to analyze the existence of traders in the Gondanglegi Traditional Market in response to the rise of e-commerce. This research employs a descriptive qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation, with traders at the Gondanglegi Market serving as the primary informants. Data analysis was conducted in three stages: pre-fieldwork, during fieldwork, and post-fieldwork, involving a comprehensive data reduction process to ensure accurate results. The findings indicate that the Gondanglegi Traditional Market has experienced a significant impact from the presence of e-commerce, specifically a decline in market activity and trader income. While the most substantial decrease in turnover occurred in non-essential sectors such as clothing and accessories, staple goods were also affected, albeit to a lesser extent. Furthermore, a lack of digital literacy among traders—who are not yet able to utilize digital platforms—has caused them to lose customers and places them at risk of losing their pivotal role in the local economy. Key words: traditional market; e-commerce; technological literacy